Zero Echo Time MRAC on FDG-PET/MR Maintains Diagnostic Accuracy for Alzheimer’s Disease; A Simulation Study Combining ADNI-Data - Ando, Takahiro; Kemp, Bradley; Warnock, Geoffrey; Sekine, Tetsuro; Kaushik, Sandeep; Wiesinger, Florian; Delso, Gaspar (Frontiers in Neuroscience, 2020)
Aim Attenuation correction using ZTE-MRI (ZTE-MRAC) has become one of the standard methods for brain-PET on commercial PET/MR scanners. Although the accuracy of the net tracer-uptake quantification based on ZTE-MRAC has been validated, that of the diagnosis for dementia has not yet been clarified, especially in terms of automated statistical analysis. The aim of this study was to clarify the impact of ZTE-MRAC on the diagnosis of Alzheimer’s disease (AD) by performing simulation study. Methods We recruited 27 subjects, who underwent both PET/CT and PET/MR (GE SIGNA) examinations. Additionally, we extracted 107 subjects from the Alzheimer Disease Neuroimaging Initiative (ADNI) dataset. From the PET raw data acquired on PET/MR, three FDG-PET series were generated, using two vendor-provided MRAC methods (ZTE and Atlas) and CT-based AC. Following spatial normalization to MNI space, we calculated the error map for each patient. We multiplied each of these 27 error maps with each of the 107 ADNI cases in MNI space. To evaluate the probability of AD in each resulting image, we calculated a cumulative t-value using a fully automated method which had been validated not only in the original ADNI dataset but several multi-center studies. In the method, PET score=1 is the 95% prediction limit of AD. PET score and diagnostic accuracy for the discrimination of AD were evaluated in simulated images using the original ADNI dataset as reference. Results PET score was slightly underestimated both in ZTE and Atlas group compared with reference CTAC (-0.0796±0.0938 vs. -0.0784±0.1724). The absolute error of PET score was lower in ZTE than Atlas group (0.098±0.075 vs. 0.145±0.122, p <0.001). A higher correlation to the original PET score was observed in ZTE vs. Atlas group (R2: 0.982 vs. 0.961). The accuracy for the discrimination of AD patients from normal control was maintained in ZTE and Atlas compared to CTAC (ZTE vs. Atlas. vs. original; 82.5% vs. 82.1% vs. 83.2% (CI 81.8–84.5%), respectively). Conclusion For FDG-PET images on PET/MR, attenuation correction using ZTE-MRI had superior accuracy to an atlas-based method in classification for dementia. ZTE maintains the diagnostic accuracy for AD.